2013
DOI: 10.1155/2013/131349
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation and Lung Function Impairment in Morbidly Obese Subjects with the Metabolic Syndrome

Abstract: Background. Obesity and asthma are associated. There is a relationship between lung function impairment and the metabolic syndrome. Whether this relationship also exists in the morbidly obese patients is still unknown. Hypothesis. Low-grade systemic inflammation associated with the metabolic syndrome causes inflammation in the lungs and, hence, lung function impairment. Methods. This is cross-sectional study of morbidly obese patients undergoing preoperative screening for bariatric surgery. Metabolic syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 37 publications
5
40
0
6
Order By: Relevance
“…Abdominal obesity is often correlated with reduced FVC and FEV (7,23). In the present study, obese adolescents had increased concentrations of abdominal fat, a fact observed during the measurement of waist circumference which was decreased significantly after exercise intervention.…”
Section: Discussionsupporting
confidence: 54%
“…Abdominal obesity is often correlated with reduced FVC and FEV (7,23). In the present study, obese adolescents had increased concentrations of abdominal fat, a fact observed during the measurement of waist circumference which was decreased significantly after exercise intervention.…”
Section: Discussionsupporting
confidence: 54%
“…However, that study did not include subjects with asthma, and the observed association was likely mediated by peripheral blood eosinophilia(47). We did not find that one particular component of the metabolic syndrome explained our results; however, WC was most consistently associated with the outcomes of interest.…”
Section: Discussionmentioning
confidence: 99%
“…There is also growing evidence that the metabolic syndrome (abdominal obesity, insulin resistance, hypertension and dyslipidaemia) is a strong risk factor for asthma, even stronger than obesity [29]. A study by VAN HUISSTEDE et al [30] showed a correlation between eosinophilia, lung function and metabolic syndrome, while no correlation was observed for BMI. The possible causal connections between endometriosis and asthma, and the metabolic syndrome and asthma could be some of the explanatory factors behind the impaired fertility of asthma patients, as both diseases are known to reduce fertility [31,32].…”
Section: Discussionmentioning
confidence: 99%